Downregulation of Heme Oxygenase 1 (HO-1) Activity in Hematopoietic Cells Enhances Their Engraftment after Transplantation. Issue 7 (July 2016) - Adamiak, Mateusz; Moore, Joseph B.; Zhao, John; Abdelbaset-Ismail, Ahmed; Grubczak, Kamil; Rzeszotek, Sylwia; Wysoczynski, Marcin; Ratajczak, Mariusz Z.
Heme oxygenase 1 (HO-1) is an inducible stress-response enzyme that not only catalyzes the degradation of heme (e.g., released from erythrocytes) but also has an important function in various physiological and pathophysiological states associated with cellular stress, such as ischemic/reperfusion injury. HO-1 has a well-documented anti-inflammatory potential, and HO-1 has been reported to have a negative effect on adhesion and migration of neutrophils in acute inflammation in a model of peritonitis. This finding is supported by our recent observation that hematopoietic stem progenitor cells (HSPCs) from HO-1 KO mice are easy mobilizers, since they respond better to peripheral blood chemotactic gradients than wild-type littermates. Based on these findings, we hypothesized that transient inhibition of HO-1 by nontoxic small-molecule inhibitors would enhance migration of HSPCs in response to bone marrow chemoattractants and thereby facilitate their homing. To directly address this issue, we generated several human hematopoietic cell lines in which HO-1 was upregulated or downregulated. We also exposed murine and human BM-derived cells to small-molecule activators and inhibitors of HO-1. Our results indicate that HO-1 is an inhibitor of hematopoietic cell migration in response to crucial BM homing chemoattractants such as stromal-derived factor 1 (SDF-1) and sphingosine-1-phosphate (S1P). Most importantly, our in vitro and in vivo animal experiments demonstrate for the first time that transiently inhibiting HO-1 activity in HSPCs by small-molecule inhibitors improves HSPC engraftment. We propose that this simple and inexpensive strategy could be employed in the clinical setting to improve engraftment of HSPCs, particularly in those situations in which the number of HSPCs available for transplant is limited (e.g., when transplanting umbilical cord blood).